Prevalence, temporal trend and associated factors with excess body weight in mothers of children under five years - NAKANO, Ricardo Paulino; Cardoso da Silva CAMINHA, Tainá; de Sousa CARVALHO, Renata Elyonara; Silva XAVIER JÚNIOR, Antônio Fernando; Lopes de ASSUNÇÃO, Monica; da Silva FERREIRA, Haroldo (Revista de Nutrição, 2023)
Objective This study aims to evaluate the prevalence, temporal trends and associated factors with excess weight in mothers of children under five years of age. Methods This is a time-series study using data from two household surveys conducted in 2005 and 2015. A total of 1,436 mothers were evaluated in 2005, and 690 were evaluated in 2015. The dependent variables were excess body weight (Body Mass Index [BMI] ≥25.0kg/m²), high percentage of Body Fat (%BF ≥33%) and abdominal obesity (waist circumference >80cm). The independent variables were the socioeconomic and demographic factors. The changes that occurred between the two surveys were expressed in percentages, and the measure of association was the Prevalence Ratio, calculated by Poisson regression, in both the crude and multivariate analyses. Results There were increases of 33.2%, 59.2% and 31.0%, respectively, for the prevalence of excess weight (PR=1.33, 95% Confidence Interval [CI]:1.21-1.46), abdominal obesity (PR=1.59, 95% CI:1.43-1.77) and high %BF (PR=1.31, 95% CI:1.07-1.60). The factors independently associated with excess weight and abdominal obesity were the highest age group (>30 years), menarche ≤12 years and higher parity (>2 children). The same was observed for high %BF, except for the loss of significance in the adjusted analysis for the variable menarche ≤12 years. Conclusion The prevalence of high body adiposity is a problem of relevant importance in the studied population and has presented an upward trend in the last 10 years. Women over 30 years and with more than two children should be given priority in prevention and control.